A Survey on Internet based Security Threats and Malicious Page Detection Techniques - Gupta, Deepali; Minj, Jasmine (International Journal of Computer Sciences and Engineering, 2025)
The vindictive site is a typical and genuine danger to digital security. Pernicious URLs have spontaneous substance like spam, phishing, drive-by misuses, and so on and draw clueless clients to wind up casualties of tricks like financial misfortune, burglary of private data, and malware establishment and so on which cause misfortunes of billions of dollars consistently. It is basic to recognize and follow up on such dangers in an opportune way. To improve the generality of malicious URL detectors, various kinds of techniques using both static and dynamic features have been explored with increasing attention in recent years. In this study, we center principally on examining the real methodologies for pernicious URL recognition procedures and work directed in the zone